2016
DOI: 10.1159/000444100
|View full text |Cite
|
Sign up to set email alerts
|

Serum Uric Acid Levels and Renal Impairment among ST-Segment Elevation Myocardial Infarction Patients Undergoing Primary Percutaneous Intervention

Abstract: Background: Elevated serum uric acid (UA) levels are associated with adverse outcomes in ST-segment elevation myocardial infarction (STEMI) patients undergoing primary percutaneous coronary intervention (PCI). However, the relation between UA and acute kidney injury (AKI) in this population is unclear. We evaluated the effect of elevated UA levels on the risk to develop AKI among consecutive STEMI patients treated with primary PCI. Methods: We performed a retrospective analysis of 1,372 consecutive patients ad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
5
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 31 publications
4
5
0
Order By: Relevance
“…The difference in uric acid levels between patients with or without CIN was 0.88 mg/dl, suggesting that even a moderate increase in uric acid levels can be of clinical relevance in this setting. Noteworthy, our findings are in agreement with previous work by Shacham et al , who performed a retrospective analysis of 1,372 consecutive patients with acute myocardial infarction and found that uric acid was an independent predictor of CIN [37]. Interestingly, these authors noted that for every 1-mg/dl increase in the uric acid concentration, the adjusted risk for CIN increased by 46% [37].…”
Section: Discussionsupporting
confidence: 92%
“…The difference in uric acid levels between patients with or without CIN was 0.88 mg/dl, suggesting that even a moderate increase in uric acid levels can be of clinical relevance in this setting. Noteworthy, our findings are in agreement with previous work by Shacham et al , who performed a retrospective analysis of 1,372 consecutive patients with acute myocardial infarction and found that uric acid was an independent predictor of CIN [37]. Interestingly, these authors noted that for every 1-mg/dl increase in the uric acid concentration, the adjusted risk for CIN increased by 46% [37].…”
Section: Discussionsupporting
confidence: 92%
“…This suggests that hyperglycemia is correlated to the occurrence of MI. In recent years, a number of studies have suggested that serum UA is closely correlated to CVD, and is one of the independent risk factors for CVD (24,25). In this study, with the increase in TG level, UA level also increased, but it was not a risk factor for MI in a population with elevated TG.…”
Section: Discussionmentioning
confidence: 41%
“…Many studies have demonstrated that serum uric acid, as an inflammatory mediator, is an independent predictor of PC-AKI in patients undergoing PCI. 6 , 7 In contrast, an increased inflammatory response is associated with decreased serum albumin. 8 Serum albumin also has antioxidant properties, and it is associated with the level of renal dysfunction.…”
Section: Introductionmentioning
confidence: 99%